Governo aberto: análise de políticas públicas sob os princípios de transparência, participação e colaboração - Daniel José Silva Oliveira (2020)
In the last decade, open government has become a topic widely discussed by national and subnational governments around the world. Despite this, both among governments and in the academic literature, there is not still a consolidated understanding of what principles should guide open government initiatives. This occur because the concept of open government has been constructed in different ways. Over time, the definitions have incorporated several principles, often under the influence of the political, social, economic, cultural and technological contexts of each moment in history, from the first records of the term to the pioneering initiatives that influenced the understanding of the meaning of open government around the world. In the contemporary academic literature on open government, the principles of transparency, participation and collaboration have been the most used, however, in most cases, it was discussed only superficially. This is one of the reasons for the scarcity of structures and guidelines for analyzing the effectiveness of open government initiatives and the influence of these principles on the public policy cycle, especially in local governments, which are the instances closest to citizens. Therefore, the main objective of this thesis is to identify whether, how and when the principles of transparency, participation and collaboration are being incorporated in the phases of the public policy cycle in local governments. To this end, a theoretical framework for the analysis of public policies was proposed, built by integrating the public policy cycle approach with the principles of transparency, participation and collaboration. The theoretical-analytical framework was applied in a case study on the open government initiative of the São Paulo City Hall, in which three different public policies were selected as units of analysis: Laboratório de Inovação Aberta (Open Innovation Laboratory - Mobilab+), Plano Municipal pela Primeira Infância (Municipal Plan for the First Childhood) and Programa Operações Urbanas (Urban Operations Program). By gathering the perspectives of the 23 key actors interviewed around the dimensions, categories and subcategories proposed in the analysis framework, it was possible to verify that, in none of the selected policies, the principles of open government were incorporated in all stages of the policy cycle and that the open government initiative was not completely institutionalized by the municipal government of São Paulo.